Optimization of a Synchronous Reluctance Motor Design Using Genetic Algorithm and On-Off Method - Mosammam, Behnam; Fahimi, Babak; Balsara, Poras (Proceedings (IEEE International Electric Machines and Drives Conference. Online), 2025)
Conventional electric machines are subject to limitations such as symmetry in design, uniform distribution of material, and legacy manufacturing techniques. Advances in 3-D printing, the advent of new composite materials, and advanced computational facilities over the past few years have introduced new opportunities that call for an rethinking design and optimization practices. These advancements enable the creation of complex machines with more efficient material usage, and better overall performance. This paper proposes an on/off magnetic optimization method for material distribution within a partitioned rotor structure and geometry for the rotor of a synchronous reluctance machine Evolutionary genetic algorithms have been used to find the best rotor geometry in terms of average torque.